Sodium chloride's effect on self‐assembly of diphenylalanine bilayer. Issue 19 (31st May 2016) - Kwon, Junpyo; Lee, Myeongsang; Na, Sungsoo
Abstract : Understanding self‐assembling peptides becomes essential in nanotechnology, thereby providing a bottom‐up method for fabrication of nanostructures. Diphenylalanine constitutes an outstanding building block that can be assembled into various nanostructures, including two‐dimensional bilayers or nanotubes, exhibiting superb mechanical properties. It is known that the effect of the ions is critical in conformational and chemical interactions of bilayers or membranes. In this study, we analyzed the effect of sodium chloride on diphenylalanine bilayer using coarse‐grained molecular dynamics simulations, and calculated the bending Young's modulus and the torsional modulus by applying normal modal analysis using an elastic network model. The results showed that sodium chloride dramatically increases the assembling efficiency and stability, thereby promising to allow the precise design and control of the fabrication process and properties of bio‐inspired materials. © 2016 Wiley Periodicals, Inc. Abstract : Understanding self‐assembling peptides becomes essential in nanotechnology, thereby providing a bottom‐up method for fabrication of nanostructures. Diphenylalanine constitutes an outstanding building block that can be assembled into various nanostructures, including 2D bilayers or nanotubes, exhibiting superb mechanical properties. It is known that the effect of the ions is critical in conformational and chemical interactions of bilayers or membranes. In this study, we analyzed the effect of sodium chloride on diphenylalanine bilayer using coarse‐grained, molecular dynamics simulations, and calculated the bending Young's modulus and the torsional modulus by applying normal modal analysis using an elastic network model. The results showed that sodium chloride dramatically increases the assembling efficiency and stability, thereby promising to allow the precise design and control of the fabrication process and properties of bio‐inspired materials.